Why isn't there more financial intermediation in developing countries? - Jonathan Conning; Michael Kevane (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper proposes to organize thinking about the opportunities for improving and extending financial markets and safety nets for the poor, by focusing on factors that may explain why the linkage of local financial networks and safety nets with the larger economy often fails or is incomplete. Understanding the nature of these impediments is the first step in proposing policies to help promote more effective linkage and intermediation. We propose four explanations for the slowness of adoption of intermediation (high costs of delegated monitoring aggravated by limited intermediary capital; lock-in and crowding out effects from local insurance arrangements, social norms against cooperation with intermediaries; and political resistance to new institutions that shift the balance of power in local polities). Of course, financial repression and weak legal systems remains important as cause of lack of intermediation. We conclude with a review of public policy for more effective intermediation.
Keywords: O16; Q14; G2; N20; 330; financial intermediation; mutual insurance; safety nets; microfinance; microcredit; Finanzintermediär; Entwicklungsländer; Privatversicherung; Mikrofinanz